2012
DOI: 10.1096/fj.11-200410
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis and increased uncoupling protein 1 in brown adipose tissue of mice fed a ketone ester diet

Abstract: We measured the effects of a diet in which D-β-hydroxybutyrate-(R)-1,3 butanediol monoester [ketone ester (KE)] replaced equicaloric amounts of carbohydrate on 8-wk-old male C57BL/6J mice. Diets contained equal amounts of fat, protein, and micronutrients. The KE group was fed ad libitum, whereas the control (Ctrl) mice were pair-fed to the KE group. Blood d-β-hydroxybutyrate levels in the KE group were 3-5 times those reported with high-fat ketogenic diets. Voluntary food intake was reduced dose dependently wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 60 publications
4
101
2
1
Order By: Relevance
“…During exercise, beside the role of irisin (45), any increase in lactate could contribute to the browning remodeling. This is also in agreement with a recent demonstration that a ketone ester-enriched diet activates BAT and increases Ucp1 expression in white adipose depot of C57BL/6J mice (46). It is also noteworthy that bHB constitutes a major energy metabolite for the newborn at a time where brown fat thermogenesis is crucial (47).…”
Section: Discussionsupporting
confidence: 91%
“…During exercise, beside the role of irisin (45), any increase in lactate could contribute to the browning remodeling. This is also in agreement with a recent demonstration that a ketone ester-enriched diet activates BAT and increases Ucp1 expression in white adipose depot of C57BL/6J mice (46). It is also noteworthy that bHB constitutes a major energy metabolite for the newborn at a time where brown fat thermogenesis is crucial (47).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, such diets raise blood cholesterol and free fatty acids, increase the risk of nephrolithiasis, and cause constipation (23,116,201). Therefore, Veech and Clarke developed and tested ingestible ketone ester compounds, which can rapidly generate ketoses exceeding 5 mM in rats and humans (37,103,195), while sparing the adverse consequences of high-fat diets. A small preliminary study indicates that oral ketone esters are safe in humans (37).…”
Section: Diagnostic and Therapeutic Targets Of Ketone Body Metabolismmentioning
confidence: 99%
“…Rodents fed these compounds acutely decrease food intake. Although these animals do not exhibit changes in body weight over an extended time period, they do become more insulin sensitive, possibly because of increased expression of uncoupling proteins in brain and brown adipose tissue (103,195). Further studies will evaluate the efficacy of these compounds in the mitigation and prevention of metabolic, myocardial, and neurological diseases in rodent and human subjects.…”
Section: Diagnostic and Therapeutic Targets Of Ketone Body Metabolismmentioning
confidence: 99%
“…Two KEs are known to be under current study: a ) 1,3-butanediol monoester of ␤ HB (KME) ( 77,(79)(80)(81)(82)(83)(84) and b ) 3GHB ( 48,85,86 ). Studies have demonstrated that orally or intravenously administered 1,3-butanediol or glycerol esters of ␤ HB are safe and well tolerated in animals ( 80,86 ), and that the orally administered 1,3-butanediol monoester is also safe and well tolerated in humans ( 79 ).…”
Section: Kesmentioning
confidence: 99%
“…Such degrees of hyperketonemia have been readily achieved by KE administration in rats, mice, pigs, and humans (78)(79)(80)(81)(82)(83)(84)(85)(86).…”
Section: +mentioning
confidence: 99%